1997
DOI: 10.1051/animres:19970302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different machine milking clusters on dairy ewes with large size teats

Abstract: Summary — Sixty-five Manchega ewes were milked with three different commercial clusters with different teatcup and claw characteristics. Clusters with a lip mouthpiece deflection close to 20 mm/kg (vs 8 mm/kg) increased the amount of machine milk (7.6-11.5%) and reduced the hand stripped milk (22.7!t0.5%) and residual milk volumes (9.7-14.9%). They also improved the milk fat (2.3-2.5%), lactose (1.0-1.4%) and dry matter (1.8%) composition, thereby potentially simplifying the machine milking routine. Milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…1). The thickness (2.34 mm) and deflection (7.5 mm) of the lip were similar to those considered suitable (2 mm and 20 mm, respectively) by Fernández et al (1997). These authors found that mouthpiece lip deflection was more important than its diameter for a good milk fractionation during milking.…”
Section: Udder Morphology and Teat-cup Designsupporting
confidence: 52%
See 1 more Smart Citation
“…1). The thickness (2.34 mm) and deflection (7.5 mm) of the lip were similar to those considered suitable (2 mm and 20 mm, respectively) by Fernández et al (1997). These authors found that mouthpiece lip deflection was more important than its diameter for a good milk fractionation during milking.…”
Section: Udder Morphology and Teat-cup Designsupporting
confidence: 52%
“…A high milk flow is also positive for good milkability because it improves milking efficiency. Milk flow during milking may be affected by udder morphology characteristics (Marnet et al, 2000), especially teat sphincter strength (Marnet et al, 2001), or the features of the cluster used, especially by the mouthpiece lip flexibility (Fernández et al, 1997). In addition, the variation of the possible combinations among the operating parameters of machine milking (vacuum level, pulsator rate and pulsator ratio) can also affect milk flows and milk fractioning (Fernández et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Annual checking and regular maintenance of milking machines constitute basic measures insufficiently applied since only 40 to 60% of the total number of machines are checked annually. Mostly, the purpose of the investigations was to study the influence of machine parameters on milking efficiency [53,141].…”
Section: Limitation Of Receptivity and Sensitivitymentioning
confidence: 99%
“…On the contrary, milk retention must be reduced through adaptation of the equipment to animal yield, teat size and flock size [53]: vacuum pump capacity, vacuum reserve, claws volume and position with regards to the liners. Automatic cluster removal systems, when they exist, must be carefully set.…”
Section: Limitation Of Receptivity and Sensitivitymentioning
confidence: 99%
“…Liner measurements were taken using a pair of callipers following the scheme described by Fernandez et al (1997). The touch point (TP) with the aid of a manual vacuum pump (Medition Precision S.L., Zaragoza, Spain), a digital vacuum gauge (DVPM-01, Delaval International AB., Tumba, Sweden) and a methacrylate cover.…”
Section: Methodsmentioning
confidence: 99%